Sprawdź i popraw błędy .

a) ( 2x+y ) ( x-2y ) - x ( x+ y ) = 2x² - 4xy + xy - 2y² - x² + xy = x² - 2xy - 2y²

b) (3a- 2b ) ( a-b ) + 2 ( a - b ) ( a- 2b ) = 3a² - 3 ab - 2ab + 2b² + 2 ( a² - 2ab - ab - 2b² ) = 5a² - 10 ab + 6b²

c) ( 4k + 1 ) ( 2k - 1 ) - (k - 1 ) (k-3 ) = 8k² - 4k + 2k - 1 - ( k² + 3k - k + 3 ) = 7k² - 4k - 4

3

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T20:06:01+01:00
A) ( 2x+y ) ( x-2y ) - x ( x+ y ) = 2x² - 4xy + xy - 2y² - x² - xy = x² - 4xy - 2y²

b) (3a- 2b)(a-b ) + 2 (a - b)(a-2b ) = 3a² - 3ab - 2ab + 2b² + 2(a² - 2ab - ab + 2b² ) = 5a² - 11 ab + 8b²

c) ( 4k + 1 ) ( 2k - 1 ) - (k - 1 ) (k-3 ) = 8k² - 4k + 2k - 1 - ( k² -3k - k + 3 ) = 7k² +2k - 4
32 4 32
2009-12-08T20:12:31+01:00
A) =2x2-4xy+xy-2y2-x2-xy=x2-4xy-2y2
b) = 3a2-3ab-2ab+2b2+2(a2-2ab-ab+2b2)=3a2-3ab-2ab+2b2+2a2-4ab-2ab+4b2= 5a2-11ab+6b2
c) =8k2-4k+2k-1-(k2-3k+k2+3)= 8k2-4k+2k-1-k2+3k-k2-3= 6k2+k-4
12 4 12
2009-12-08T20:14:35+01:00
a ) ( 2x + y ) ( x - 2y ) - x ( x + y ) = 2x² - 4 xy + xy - 2y² - x² - xy = x² - 4 xy - 2y²

b ) ( 3a - 2 b ) ( a - b ) + 2 ( a - b ) ( a - 2b ) = 3a² - 3 ab - 2ab + 2b² + 2 ( a² - 2ab - ab + 2b² ) = 5a² - 11 ab + 4 b²

c) ( 4k + 1 ) ( 2k - 1 ) - (k - 1 ) (k-3 ) = 8k² - 4k + 2k - 1 - ( k² - 3k - k + 3 ) = 7k² + 2k - 4
25 4 25